Radio observations of the double-relic galaxy cluster Abell 1240 - Hoang, D.; Shimwell, T.; van Weeren, R.; Intema, Hubertus; Rottgering, H.; Andrade-Santos, F.; Akamatsu, H.; Bonafede, A.; Brunetti, G.; Dawson, W.; Golovich, N.; Best, P.; et al. (Oxford University Press, 2018)
We present LOw Frequency Array 120–168 MHz images of the merging galaxy cluster Abell 1240 that hosts double radio relics. In combination with the Giant Metrewave Radio Telescope 595–629 MHz and Very Large Array 2–4 GHz data, we characterized the spectral and polarimetric properties of the radio emission. The spectral indices for the relics steepen from their outer edges towards the cluster centre and the electric field vectors are approximately perpendicular to the major axes of the relics. The results are consistent with the picture that these relics trace large-scale shocks propagating outwards during the merger. Assuming diffusive shock acceleration, we obtain shock Mach numbers of M=2.4 and 2.3 for the northern and southern shocks, respectively. For M≲3 shocks, a pre-existing population of mildly relativistic electrons is required to explain the brightness of the relics due to the high (>10 per cent) particle acceleration efficiency required. However, for M≳4 shocks the required efficiency is ≳1 per cent and ≳0.5 per cent, respectively, which is low enough for shock acceleration directly from the thermal pool. We used the fractional polarization to constrain the viewing angle to ≥53 ± 3° and ≥39 ± 5° for the northern and southern shocks, respectively. We found no evidence for diffuse emission in the cluster central region. If the halo spans the entire region between the relics (∼1.8 Mpc) our upper limit on the power is P1.4 GHz=(1.4±0.6)×1023W Hz−1 which is approximately equal to the anticipated flux from a cluster of this mass. However, if the halo is smaller than this, our constraints on the power imply that the halo is underluminous.